Selective arrangement of ubiquitinated and D1 protein-containing nucleosomes within the Drosophila genome. - Levinger, L.; Varshavsky, A. (Cell, 1982)
We have a new approach, two-dimensional hybridization mapping of nucleosomes, to compare the structures of mononucleosomes from different regions of the Drosophila melanogaster genome. Approximately one in two nucleosomes of the transcribed copia and heat-shock 70 (hsp 70) genes in nonshocked cultured cells contains ubiquitin-H2A (uH2A) semihistone, a covalent conjugate of histone H2A and a small protein, ubiquitin. In striking contrast, less than one in 25 nucleosomes of tandemly repeated, nontranscribed 1.688 satellite DNA contains uH2A, suggesting that most of the nucleosomal uH2A is located in transcribed genes. Approximately 25% of all nucleosomes are ubiquitinated in nonsynchronized cultured Drosophila cells. The hsp 70 genes in nonshocked cells occur in nucleosomes, are greatly enriched in uH2A and are not digested preferentially by staphylococcal nuclease. In contrast, the same genes in chromatin from heat-shocked cells are highly sensitive to staphylococcal nuclease and no longer possess nucleosomal organization recognizable with this probe. Histone ubiquitination in transcribed nucleosomes may prevent formation of higher order chromosomal structures by modifying nucleosome-nucleosome interactions. The observed loss of nucleosomal organization in very actively transcribed genes, such as the hsp 70 genes in shocked cells, may be related to the recent finding that ubiquitin conjugates are substrates for the cytoplasmic ATP-dependent proteolytic system. We have also found that 1.688 satellite mononucleotomes contain a specific approximately 50,000 dalton nonhistone protein, D1, in addition to being extremely under-ubiquitinated. D1 may be involved in formation of the highly compact structure of satellite heterochromatin.